After-discharge activity as a basis to change intraoperative mapping protocol for functionally significant brain areas - M. G. Podgurskaya; D. S. Kanshina; A. V. Dimertsev; M. V. Alexandrov; S. S. Nikitin (Эпилепсия и пароксизмальные состояния, 2023)
Background. After-discharge (AD) activity is a pattern that differs from background corticography, represented by rhythmic stereotypical slow waves and/or repetitive spike discharges with ≥1 Hz frequency, recorded after cessation of electrical stimulation and lasting for more than 2 seconds. Despite the accumulated experience in the field of intraoperative neuromonitoring, there is no unified protocol for high-frequency stimulation of cortical functional areas (FAs) upon the AD event.Objective: to demonstrate a need to change the intraoperative FAs mapping protocol in patients with brain tumor on awakening in cases of AD recording.Material and methods. Two clinical cases of awake surgical functional mapping followed by resection of the brain tumor are presented. Multimodal monitoring included high-frequency stimulation according to the approved intrahospital protocol with maximum stimulation force of auditory-speech zones of 2.5 mA, electrocorticography, and subcortical dynamic mapping.Results. In the first case, AD was registered while FAs mapping in a patient with a history of one epileptic seizure, upon reaching the maximum stimulation force of 2.5 mA, that was replaced by recording focal epileptiform activity with the following evolution to ictal generalized event and development of intraoperative convulsive seizure. In the second patient with a history of recurrent epileptic seizures, AD with spatiotemporal evolution of the pattern development of clinical ictal event was registered with stimulation at 2.5 mA. In both cases, the appearance of AD required to change mapping protocol with a stepwise decrease in stimulus strength to obtain cortical FAs data.Conclusion. Registration of AD is the basis for changing the protocol of high-frequency cortical stimulation in surgical treatment of brain tumor FAs.